2015
DOI: 10.1007/s12026-015-8765-7
|View full text |Cite
|
Sign up to set email alerts
|

Th9 and Th22 immune response in young patients with type 1 diabetes

Abstract: Th17, Th22 and Th9 are recently discovered effector populations that may contribute to the pathogenesis of autoimmune and inflammatory diseases. The presented study aimed to investigate the link between Th22 and Th9 subsets in type 1 diabetes, as this disease involves different subsets of CD4+ T lymphocytes. The study groups consisted of 23 patients with type 1 diabetes and 11 healthy individuals. All subjects had CD4+IL-22 Th22 and CD4+IL-9 Th9 lymphocytes investigated by flow cytometry. In addition, the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…In the present study, there was no statistical difference in Th22 frequency between MG patients and HCs, while a statistically significant decrease in Th22 was found post-TE. The role of Th22 cells in the pathogenesis of autoimmune diseases has been confirmed in many studies [16,[43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 79%
“…In the present study, there was no statistical difference in Th22 frequency between MG patients and HCs, while a statistically significant decrease in Th22 was found post-TE. The role of Th22 cells in the pathogenesis of autoimmune diseases has been confirmed in many studies [16,[43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 79%
“…IL‐5 is important for the proliferation of CD19 + IgM + B cells in NOD mice and stimulates the secretion of IL‐10 by B cells, which exerts a robust suppressive effect on the pathogenesis of diabetes . IL‐9 expression is increased in the serum of patients with T1D; it is correlated with the size of Th9 effector subpopulations and predicts HbA1c values, but the role of IL‐9 in T1D is uncertain . The IL‐4 and IL‐13 cytokines, encoded by adjacent genes, transduce signals via a partially shared receptor (IL‐4Rα), and their effects in T1D have been unveiled in a number of studies.…”
Section: Classical Cytokines With Anti‐inflammatory Rolesmentioning
confidence: 99%
“…13 IL-9 expression is increased in the serum of patients with T1D; it is correlated with the size of Th9 effector subpopulations and predicts HbA1c values, but the role of IL-9 in T1D is uncertain. 14,15 The IL-4 and IL-13 cytokines, encoded by adjacent genes, transduce signals via a partially shared receptor (IL-4Ra), and their effects in T1D have been unveiled in a number of studies.…”
Section: Type-2 Cytokinesmentioning
confidence: 99%
“…In another study, it was also observed a link between Th22 and Th9 cells in DM1 patients. These patients showed an increase in Th9 and Th22 cells, as well as increased serum levels of IL-9 and IL-22 compared with healthy individuals [112].…”
Section: Based On Cytokines Profile and Effector Function Cd4 + T Hementioning
confidence: 82%